2015
DOI: 10.1111/age.12334
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia‐associated transcription factor mutations are associated with white‐spotted coat color in swamp buffalo

Abstract: SummaryA candidate gene analysis of the microphthalmia‐associated transcription factor (MITF) gene was used in an attempt to identify the genetic basis for a white‐spotted coat color phenotype in the Asian swamp buffalo (Bubalus bubalis carabanensis). Ninety‐three buffaloes—32 solid, 38 spotted and 23 white individuals—were Sanger‐sequenced for all MITF exons as well as highly conserved intronic and flanking regions. MITF cDNA representing skin and iris tissue from six spotted, nine solid and one white buffalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
(13 reference statements)
1
19
0
Order By: Relevance
“…The body appearance and skin color of buffaloes in the present study conform to swamp buffaloes from Dehong, Diandongnan, Guizhou, Dechang, and Xilin, China (Yongwang et al 2010), swamp buffaloes from South and East Kalimantan, Indonesia (Hamdan et al 2010;Lita 2009), swamp buffaloes from Trishal, Bangladesh (Siddiquee et al 2010) and water buffaloes from the United Arab Emirates (Presicce 2016). The coat colors in the four regions (NK, EK, SK, and PT) agreed with Toraja buffalo studies from Tana Toraja, Indonesia (Yusnizar et al 2015), swamp buffaloes from China, Vietnam, and Laos (Sun et al 2019) where swamp buffalo coats were generally dominated by black to grayish . Horn patterns and chevron patterns in KBuf.…”
Section: Qualitative Characteristicssupporting
confidence: 79%
“…The body appearance and skin color of buffaloes in the present study conform to swamp buffaloes from Dehong, Diandongnan, Guizhou, Dechang, and Xilin, China (Yongwang et al 2010), swamp buffaloes from South and East Kalimantan, Indonesia (Hamdan et al 2010;Lita 2009), swamp buffaloes from Trishal, Bangladesh (Siddiquee et al 2010) and water buffaloes from the United Arab Emirates (Presicce 2016). The coat colors in the four regions (NK, EK, SK, and PT) agreed with Toraja buffalo studies from Tana Toraja, Indonesia (Yusnizar et al 2015), swamp buffaloes from China, Vietnam, and Laos (Sun et al 2019) where swamp buffalo coats were generally dominated by black to grayish . Horn patterns and chevron patterns in KBuf.…”
Section: Qualitative Characteristicssupporting
confidence: 79%
“…Although several previous studies have reported specific association of SNPs of MITF in cattle [ 18 ], buffalo [ 19 ], and dog [ 20 ], there is virtually no information on the SNPs of MITF in poultry, including duck. The present study, to the best of our knowledge, is the first to report an SNP-specific association analysis to discriminate between Asian ducks with black and white plumage color.…”
Section: Discussionmentioning
confidence: 99%
“…A missense mutation (p. Arg210Ile) in the bovine MITF gene traced to chromosome 22 was shown to be the cause of German White Fleckvieh syndrome, which is dominantly inherited in Fleckvieh cattle and associated with hypopigmentation [ 18 ]. In a recent study on swamp buffalo, a nonsense mutation (p. Arg110*) in exon 3 and a donor splice-site mutation (p. Glu281_Leu282Ins8) in intron 7 of MITF were mapped to chromosome 22, both of which are associated with white-spotted coat color [ 19 ]. Similarly, in six Ethiopian cattle populations with different environmental adaptation, it was shown that coat color variation was associated with MITF , and a high genetic distance was observed between spotted and unspotted populations [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now genetic studies have mainly addressed genetic diversity (Barker et al ; Lei et al ; Kumar et al ; Zhang et al ; Colli et al ) and identification of genes and molecular markers that are associated with desirable traits (de Camargo et al ; Yusnizar et al ; Iannaccone et al ; Liu et al ), but to date only a few epigenetic studies have been carried out on water buffalo (Verma et al ; Agrawal et al ; Sharma et al ).…”
Section: Introductionmentioning
confidence: 99%